Retrospective volume analysis of bone remodeling after tooth extraction with and without deproteinized bovine bone mineral insertion. Issue 9 (5th October 2015) - Sbordone, Carolina; Toti, Paolo; Martuscelli, Ranieri; Guidetti, Franco; Ramaglia, Luca; Sbordone, Ludovico
Abstract: Objectives: The aim of the study was to analyze volume changes of post‐extractive sockets grafted with or without deproteinized bovine bone mineral (DBBM) and a resorbable barrier. Materials and methods: This retrospective analysis utilized patients who had undergone tooth extraction. Sites, one per patient, were allocated to two groups: post‐extractive non‐grafted sockets (NG) and post‐extractive grafted sockets with DBBM and resorbable barrier insertion (G). Maximal primary soft tissue closure was sought for both procedures. Before extraction and 6 months later, three‐dimensional features of the sockets (linear indexes, areas, and volumes) and outcome variables at 6 months (volume‐ and surface changes) were acquired through computer tomography scans. Intra‐ and inter‐group comparisons of the outcome variables were performed. Nonparametric tests were applied with a level of significance set at P < 0.01. Results: Twenty‐four sites, 9 grafted and 15 ungrafted, were enrolled. Between baseline and the 6‐month evaluation, significant bone volume loss, superior surface shrinkage, and height reduction were registered for the G (72 mm 3, 76 mm 2, and 0.5 mm, respectively) and the NG group (274 mm 3, 87 mm 2, and 1.8 mm, respectively) with all P ‐values ≤ 0.0039. A significant difference, regarding the percentage of the volume change, was registered between the two procedures with a volume loss of 9.9% for the grafted sockets and 34.8% for the ungrafted ones ( P ‐value = 0.0073). Conclusion: Grafting of the sockets with DBBM and a resorbable barrier insertion seemed to reduce negative osseous remodeling in the short term when compared to that of the ungrafted sockets.